Access to Disability-related Healthcare among People with Visual Disability in India: Evidence from a National Sample Survey - Ashok Kumar; Praveena Tandon; Gaurav Meratwal (Indian Journal of Community Medicine)
Background: Despite progress, there are still gaps and inequalities in achieving universal health coverage (UHC), particularly among marginalized populations such as people with visual disability (VD). This study aimed to evaluate access to disability-related healthcare among people with VD in India. Methods: Data from the Survey of Persons with Disabilities in India, the 76th round of the National Sample Survey (NSS), which was conducted between July 2018 and December 2018, were used in this study. Binomial logistic regression was used to find the association between access to disability-related healthcare and sociodemographic characteristics. Results: The prevalence of VD in the general population was 0.23%. About 15% of people with VD did not have access to healthcare for disability. Access was lower in the older age group (Adjusted Odds Ratio (AOR) =0.68) than in the younger age group, females (AOR = 0.89), persons with low literacy (AOR = 0.72), low consumption expenditure (AOR = 0.60), and people belonging to the scheduled tribes (STs) (AOR = 0.57). Affordability was the leading reason for poor accessibility. About 55% of people with VD had zero out-of-pocket expenditure (OOPE), 35.8% had monthly OOPE below INR 1000, and 1.3% had monthly OOPE INR >5000. Conclusion: The study found gaps in access to healthcare in people with VD in India. This population is falling behind in the core elements of UHC, i.e. affordability and inequality. India should adopt a comprehensive strategy that includes age-specific interventions, improved rural access, measures for socioeconomic equity, gender sensitivity, and expanded public health insurance coverage and social security schemes for people with VD.